Efektivitas Media Spinning Wheel terhadap Hasil Belajar Siswa pada Materi Tajwid - Hanum Hestina; Syarifatul Hayati; Laili Ramadani (Pusat Riset dan Inovasi Nasional, 2025)
Spinning wheel learning media is a medium that can help make it easier for teachers to deliver material to students because of its unique shape such as a circle that can be moved and there are tajweed rules in it, making students enthusiastic when learning using this media. After observations of grade IV students and interviews with teachers at MIS Al-Khair Padang Panjang, problems were found, namely some students felt bored and sleepy due to a lot of discussion and long explanation of the material. In addition, the limitations of learning media and learning tools that make it difficult for students to understand learning materials. This study aims to determine the increase in the average increase in student learning outcomes and help teachers and students to work together in the learning process. The research method used is a quantitative research method that emphasizes its analysis on numerical data (numbers) processed by statistical methods. While the type of research uses experimental research methods. The results showed that there was an increase in the average student learning outcomes of tajweed material in Al-Qur`an Hadith class IV MIS Al Khair Padang Panjang after using spinning wheel media with an average value of 45.83 increasing to 81,80.